Estudio de Factibilidad para la Creación de un Complejo Deportivo en el Barrio de San Juan del Cantón Pujilí - Comina Anchatipán, Byron Alexis (2022)
The present work entitled "Feasibility study for the creation of a sports complex in the neighborhood of San Juan del Cantón Pujilí" aims to describe feasibility studies from various approaches and perspectives and their importance in business profitability; carry out a market study, an administrative and philosophical proposal that contribute to the business and demonstrate the feasibility generated by the project through the study and financial evaluation. The methodology used is based on a quantitative approach, which uses the survey as a data collection technique through the use of a questionnaire addressed exclusively to parents. The study population is 488,716 people, while the sample is 382 individuals (men and women) whose age ranges from 6 to 60 years. The financial evaluation determines its viability with a net present value of USD 345.00 and an internal rate of return of 22.5%.